Understanding the Intra‐Molecular Proton Transfer of Octahydrotriborate and Exploring the Dehydrogenation Pathways of NH4B3H8 by DFT Calculations. Issue 3 (11th February 2021) - Gao, Peng; Zhang, Jie
Abstract: The intra‐molecular proton transfer of octahydrotriborate, [B3 H8 ] −, is discovered by density functional theory (DFT) computational studies; such a transfer can largely impact its dehydrogenation pathways. The DFT calculation results further disclose the generation of another triborane intermediate product, B3 H9, which is formed via inter‐molecular proton transfer from [NH4 ] + to [B3 H8 ] − . Additionally, this intermediate product is unstable and can release hydrogen easily, as the corresponding energy barrier via this pathway is only 12.0 kcal mol −1 . Such a relative energy is much lower than that of the routinely raised pathway, which mainly depends on the dihydrogen interaction between the B − H δ − and N − H δ + . This new mechanism is able to explain several experimental observations involving the dehydrogenation of NH4 B3 H8 . Moreover, the detailed dehydrogenations of NH4 B3 H8 in different states are also studied, and the role of chemical environment during dehydrogenation is demonstrated. Abstract : The dehydrogenation pathways of NH4 B3 H8 are explored by DFT calculations, and related intermediate products are identified. Moreover, the intra‐molecular proton transfer of octahydrotriborate is revealed to be crucial for its dehydrogenation.